2011
DOI: 10.1152/jn.00058.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional control of BK channel open probability by CAMKII and PKC in medial vestibular nucleus neurons

Abstract: van Welie I, du Lac S. Bidirectional control of BK channel open probability by CAMKII and PKC in medial vestibular nucleus neurons. J Neurophysiol 105: 1651-1659, 2011. First published February 9, 2011 doi:10.1152/jn.00058.2011.-Large conductance K ϩ (BK) channels are a key determinant of neuronal excitability. Medial vestibular nucleus (MVN) neurons regulate eye movements to ensure image stabilization during head movement, and changes in their intrinsic excitability may play a critical role in plasticity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 80 publications
4
44
0
1
Order By: Relevance
“…2A, right, dark blue). Cav2.2 channels have a much higher single channel conductance, maximal P o , and inactivate slowly 5 , 6 , 10 , 12 . A single Cav2.2 channel at 20 nm distance from a KCa1.1 channel was thus able to increase the KCa1.1 P o to 0.14, or twice that of a single Cav3.2 channel (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…2A, right, dark blue). Cav2.2 channels have a much higher single channel conductance, maximal P o , and inactivate slowly 5 , 6 , 10 , 12 . A single Cav2.2 channel at 20 nm distance from a KCa1.1 channel was thus able to increase the KCa1.1 P o to 0.14, or twice that of a single Cav3.2 channel (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The spike rate adaptation with lower amplitude after hyperpolarization of cerebellar granule cells might result from deactivation of large-conductance K + (BK) channels (48) due to the decreased activity of calcium/calmodulin-dependent protein kinase II in Ube3a m−/p+ mice (5). Previous in vivo analysis in Ube3a m−/p+ mice showed that aberrant Purkinje cell firing consisted of the increased frequency and rhythmicity of simple spikes (49).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, however, that UVD affects excitability via signaling pathways distinct from those critical for firing rate potentiation. The downstream consequence of the reduced [Ca2+] and CaMKII levels that trigger FRP is a marked reduction of BK currents (Nelson et al, 2005; van Welie and du Lac 2011). To determine whether BK channels are affected by UVD, we assessed the actions of the specific BK channel antagonist iberiotoxin (IBTX) on MVN neuronal excitability, as described previously (Nelson et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…SK-type calcium activated potassium conductances exert a predominant influence on excitability gain in MVN neurons (Smith et al, 2002) but do not play a role in firing rate potentiation (Nelson et al, 2003). Peripheral vestibular dysfunction additionally induces dynamic changes in glucocorticoids (Cameron and Dutia, 1999), nitric oxide (Anderson, et al, 1998; Park and Jeong, 2000), and neurotransmitter levels (Yamanaka et al, 2000; Vibert et al, 2000; Johnston et al, 2001; Bergquist et al, 2008) which may enhance or counteract the effects of firing rate potentiation on MVN neuronal excitability, possibly via alterations in sodium channel gating, subthreshold potassium currents, or enzymatic regulation of BK channels (Shao et al, 2009; van Welie and du Lac, 2011). Heterogeneity of physiological factors that modulate spontaneous firing rate and gain differentially across MVN cell types (Shin et al, 2011) could account for differences in our study between the time courses and magnitudes of plasticity in measures of excitability and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation